1997
DOI: 10.1094/cchem.1997.74.4.476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Distribution and (1→3)(1→4)‐β‐d‐Glucan Content of Consecutive Extracts of Various Oat and Barley Cultivars

Abstract: The content and molecular weight (MW) of β‐glucan in extracts from a selection of oat and barley cultivars were compared using flow‐injection analysis and high‐performance size‐exclusion chromatography. From 60 to 75% of the β‐glucan was extracted from oat and waxy barley by hot water (90°C) containing heat‐stable α‐amylase, whereas just 50–55% was extracted from nonwaxy barley. Consecutive extractions with hot water and dimethylsulfoxide (DMSO) extracted 65% (nonwaxy barley) or 75–80% (oat and waxy barley) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(88 citation statements)
references
References 12 publications
7
80
1
Order By: Relevance
“…Oat β-glucan has a higher molecular weight than barley or rye β-glucan (Beer et al 1997). Nutritionally, β-glucan is a dietary fiber not degraded by digestive enzymes.…”
Section: Kaukovirta-norja a Et Al Germination Of Oatmentioning
confidence: 99%
See 1 more Smart Citation
“…Oat β-glucan has a higher molecular weight than barley or rye β-glucan (Beer et al 1997). Nutritionally, β-glucan is a dietary fiber not degraded by digestive enzymes.…”
Section: Kaukovirta-norja a Et Al Germination Of Oatmentioning
confidence: 99%
“…However, the content and properties of β-glucans are important also in malted oat products if the cholesterol lowering and other functional effects of fiber are to be maintained. Especially, the ability of oat products to develop highly viscous matrices is known to depend on the molecular weight and viscosity of β-glucans, and furthermore, this ability is known to be influenced by processing (Beer et al 1997, Zhang et al 1998, Gallaher et al 1999. Therefore, Wilhelmson et al (2001) developed a short malting process for oat aiming to retain high β-glucan content also in malted oat.…”
Section: Kaukovirta-norja a Et Al Germination Of Oatmentioning
confidence: 99%
“…Although the estimates of the PD of the barley bglucans vary considerably between different studies (Jin et al 2004), careful assays of native, undegraded, b-glucans revealed a mol. wt of several hundred thousands to a few millions (Wood et al 1991;Beer et al 1997;Knuckles et al 1997;Irakli et al 2004), corresponding to a PD of 2-15 thousands units. Degradation of highly polymeric b-glucans by b-glucanase involves an initial phase during which the long chains are rapidly cleaved into a polydisperse population of fragments, but production of oligosaccharide end-products is negligible; whereas the subsequent decrease in the PD is slower (Gómez et al 1997;Carbonell et al 1998).…”
Section: Clues From In Vitro Modelingmentioning
confidence: 99%
“…Of these, arabinoxylans and -glucans constitute major parts. For example, wheat, triticale, and rye enrich arabinoxylans [8], whereas oats and barley contain more -glucans [7,19]. Generally, the viscous properties of the polysaccharides make them diYcult to be digested by domestic animals.…”
Section: Animal Feedstocksmentioning
confidence: 99%